Testosterone undecanoate and depo medroxyprogesterone acetate induced azoospermia through increased expression of spermatogenic cell caspase 3 (Medical Journal of Indonesia, 2008)
The administration of a combination of testosterone undecanoate (TU, a long-acting androgen) and depo-medroxyprogesterone acetate (DMPA) were investigated in term of suppression of rat sperm concentration in vivo to azoospermia through increasing activity of spermatogenic cell caspase 3. Adult Sprague Dawley rats received TU and DMPA of 2.5 mg and 1.25 mg, respectively, a regimen known to rapidly reduce intra testicular testosterone and to produce azoospermia within 12 weeks. Caspase 3 positive sperm cells increased compared with control levels during 6 weeks post-injection and increased further through 60 weeks. Immunohistochemistry for caspase 3 revealed that spermatocytes represented the predominant caspase 3 positive germ cells. Modest immunoreactivity for caspase-3 was localized to nuclear region of the germ cells of control and treated testes. Immunohistochemistry study revealed significantly increased caspase-3 expression in nuclei of germ cells during administration of TU+DMPA to rats. Additionally, the caspase 3 content was significantly increased in germ cells during rats were administered TU+DMPA (453.90±84.88 cells/200 seminiferous tubules) and caspase 3 significant increase in immunoreactivity was localized to the nuclei of spermatogonia, spermatocytes, and spermatids. Taken together, these results indicated that azoospermia due to reduced intratesticular testosterone concentration was caspase-3 activation dependent and suggested that the increase in active caspase-3 in the nucleus may be involved in the induction of decreased sperm production. (Med J Indones 2008; 17: 149-56)